Man enough to do it? Girls and non-traditional subjects in lower secondary eduction - Emer Smyth; Merike Darmody (The Economic and Social Research Institute (ESRI), 2007)
This article examines the processes influencing the choice of non-traditional subjects by girls in lower secondary education in the Republic of Ireland. In particular, we focus on the traditionally 'male' technological subjects, namely, Materials Technology (Wood), Metalwork and Technical Graphics. Analyses are based on detailed case-studies of twelve secondary schools, placing them in the context of national patterns of subject take-up. Strong gender differentiation persists in the take-up of these technological subjects. Commonalities are evident across schools in the way in which the subjects are constructed as 'male'. However, some students, both female and male, actively contest these labels, and school policy and practice regarding subject provision and choice can make a difference to take-up patterns. It is argued that the persistent gendering of subjects has implications for the skills acquired by students, their engagement in education, and the education, training and career opportunities open to them on leaving school.
Keywords: 330; Gender; subject choice; stereotyping; lower secondary education; Frauenbildung; Bildungsverhalten; Bildungsniveau; Irland